Rediseño de empaques y embalajes de artesanías de la cerámica olmos para difundir la imagen del producto en los habitantes de la ciudad de Pujilí - Casnanzuela Pachucho, Fanny Azucena (2015)
The research project, "REDESIGN OF HANDICRAFTS PACKAGINGS AND WRAPPING OF OLMOS CERAMIC TO SPREAD THE PRODUCT IMAGE IN THE RESIDENTS OF THE PUJILÍ CITY", is considered to be the initial diagnosis of the craft of the province through the determination of the current situation of the artisan and its potential for commercialization. Generating a market study done surveys applied to the Olmos ceramic customers….